Paramagnetic Ionic Liquid/Metal Organic Framework Composites for CO2/CH4 and CO2/N2 Separations - Ferreira, Tiago J. (2020)
IF/01016/2014 SFRH/BD/139627/2018 PTDC/CTMCTM/30326/2017 PTDC/EQU-EQU/32050/2017 PTDC/FIS-MAC/28157/2017 UIDB/50006/2020 UIDP/50006/2020